2013
DOI: 10.1128/aac.00780-13
|View full text |Cite
|
Sign up to set email alerts
|

Differential Adaptive Responses of Staphylococcus aureus to In Vitro Selection with Different Antimicrobial Peptides

Abstract: We subjected Staphylococcus aureus ATCC 29213 to serial passage in the presence of subinhibitory concentrations of magainin 2 and gramicidin D for several hundred generations. We obtained S. aureus strains with induced resistance to magainin 2 (strain 55MG) and gramicidin D (strain 55GR) that showed different phenotypic changes in membrane properties. Both exhibited a change in membrane phospholipid content and an increase in membrane rigidity, while an alteration in net charge compared to that of the control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…They analyzed the effects of sub-lethal concentrations of two AMP, magainin 2 and gramicidin D, on the rise of resistant strains of S. aureus , and found that the two peptides induced different resistance strategies that result in an increase of membrane rigidity (Shireen et al, 2013). …”
Section: Main Mechanisms Of Resistance To Amps In Bacteriamentioning
confidence: 99%
“…They analyzed the effects of sub-lethal concentrations of two AMP, magainin 2 and gramicidin D, on the rise of resistant strains of S. aureus , and found that the two peptides induced different resistance strategies that result in an increase of membrane rigidity (Shireen et al, 2013). …”
Section: Main Mechanisms Of Resistance To Amps In Bacteriamentioning
confidence: 99%
“…Human β-defensin (HBD-3) triggers the upregulation of the cell wall stress response pathway in S. aureus to counteract HBD-3-induced perturbation of peptidoglycan synthesis (13). Exposure of S. aureus to sub-lethal concentrations of magainin 2 and gramicidin D promotes to resistance to these AMPs through the enhancement of membrane rigidity (218). Changes in membrane fluidity induced by incorporation of longer chain unsaturated fatty acids into the lipid bilayer (resulting in increased membrane fluidity), or carotenoid staphyloxanthin pigment (resulting in increased membrane rigidity), promotes S. aureus resistance to platelet-derived AMPs (tPMPs), or polymyxin B and human neutrophil defensin 1, respectively (219, 220).…”
Section: Bacterial Amp Resistance Mechanismsmentioning
confidence: 99%
“…Similarly, a previous study showed that a less fluid membrane could mediate the resistance to daptomycin in E. faecalis and E. faecium (111). It has been documented that in Listeria monocytogenes the resistance to nisin is accompanied by changes in the constituent fatty acids of the membrane, which increase its rigidity (112). Moreover, an increase in the S. aureus membrane rigidity was a common characteristic in a strain with induced resistance to magainin 2 and another to gramicidin (113).…”
Section: Cellular Surface Remodellingmentioning
confidence: 64%